2020
DOI: 10.1186/s12879-020-05107-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of cerebral malaria and TNF-α levels: a systematic review

Abstract: Background: Cerebral malaria is the most severe form of infection with Plasmodium falciparum characterized by a highly inflammatory response. This systematic review aimed to investigate the association between TNF-α levels and cerebral malaria. Methods: This review followed the Preferred Reporting of Systematic Review and Meta-analyses (PRISMA) guidelines. The search was performed at PubMed, LILACS, Scopus, Web of Science, The Cochrane Library, OpenGrey and Google Scholar. We have included studies of P. falcip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 57 publications
(150 reference statements)
1
16
0
2
Order By: Relevance
“…This supports the contention that P. berghei-induced malaria infection in mice is associated with an increase in TNF-a as reviewed by some authors. 43 Are interleukins 5 and 6 affected by P. berghei-induced malaria infection? The IL-6 is a pleiotropic cytokine that can be produced by many cell types, including T cells, monocytes and endothelial cells, all of which are key to the lesion of CM.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the contention that P. berghei-induced malaria infection in mice is associated with an increase in TNF-a as reviewed by some authors. 43 Are interleukins 5 and 6 affected by P. berghei-induced malaria infection? The IL-6 is a pleiotropic cytokine that can be produced by many cell types, including T cells, monocytes and endothelial cells, all of which are key to the lesion of CM.…”
Section: Discussionmentioning
confidence: 99%
“…Highly circulating TNF-α levels also detected in patients with uncomplicated and severe P. falciparum infections (Perera et al, 2013). Although a recently published systematic review had associated the increase in TNF-α level with cerebral malaria caused by P. falciparum in humans, however, the study reported that current evidence is imprecise and inconsistent that requires more observational studies to prove it (Leão et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review that included 34 studies showed that elevated levels of TNF-α could be associated with cerebral malaria caused by P. falciparum, but the results are inconsistent. Most studies included a relatively small number of patients; further research is required [43]. In addition, there is a link between polymorphism within the TNF promoter region, parasitemia, and malaria severity.…”
Section: Cytokine Network In Malariamentioning
confidence: 99%